Analysis of Common Mistakes in English Writing Among Law Students at UIN Syarif Hidayatullah - Sahla Izzati Izzati (Universitas Muhammadiyah Lampung, 2024)
This study aims to analyze the errors that appear in the English writing of third-semester students of the Law Study Program at UIN Syarif Hidayatullah in the English MKDU course. Using a descriptive qualitative approach, this research involved 24 students who were asked to spontaneously write a short essay on a general academic topic. The data were analyzed using the Dulay, Burt, and Krashen error taxonomy, which includes omission, addition, misformation, and misordering, complemented by an analysis of vocabulary, spelling, and coherence aspects. The results show that grammar errors are the most dominant category, followed by vocabulary errors, sentence structure, spelling, and paragraph coherence. The findings also reveal that Indonesian language interference, low mastery of basic grammar, limited exposure to English, and dependence on translation tools are the main factors causing these errors. Overall, this research emphasizes the need for a more integrated writing learning approach that focuses on developing linguistic competence, rhetorical strategies, and meaningful feedback to improve the writing skills of non-English language students.